Antibacterial, Cytocompatible, Sustainably Sourced: Cellulose Membranes with Bifunctional Peptides for Advanced Wound Dressings. Issue 7 (11th March 2020) - Weishaupt, Ramon; Zünd, Janina N.; Heuberger, Lukas; Zuber, Flavia; Faccio, Greta; Robotti, Francesco; Ferrari, Aldo; Fortunato, Giuseppino; Ren, Qun; Maniura‐Weber, Katharina; Guex, Anne Géraldine
Abstract: Progressive antibiotic resistance is a serious condition adding to the challenges associated with skin wound treatment, and antibacterial wound dressings with alternatives to antibiotics are urgently needed. Cellulose‐based membranes are increasingly considered as wound dressings, necessitating further functionalization steps. A bifunctional peptide, combining an antimicrobial peptide (AMP) and a cellulose binding peptide (CBP), is designed. AMPs affect bacteria via multiple modes of action, thereby reducing the evolutionary pressure selecting for antibiotic resistance. The bifunctional peptide is successfully immobilized on cellulose membranes of bacterial origin or electrospun fibers of plant‐derived cellulose, with tight control over peptide concentrations (0.2 ± 0.1 to 4.6 ± 1.6 µg mm −2 ). With this approach, new materials with antibacterial activity against Staphylococcus aureus (log4 reduction) and Pseudomonas aeruginosa (log1 reduction) are developed. Furthermore, membranes are cytocompatible in cultures of human fibroblasts. Additionally, a cell adhesive CBP‐RGD peptide is designed and immobilized on membranes, inducing a 2.2‐fold increased cell spreading compared to pristine cellulose. The versatile concept provides a toolbox for the functionalization of cellulose membranes of different origins and architectures with a broad choice in peptides. Functionalization in tris‐buffered saline avoids further purification steps, allowing for translational research and multiple applications outside the field of wound dressings. Abstract : Bifunctional peptides, combining an antimicrobial peptide and a cellulose binding peptide (CBP), or a cell adhesion peptide (RGD) and a CBP, are successfully designed and immobilized on cellulose membranes. The modular design concept is highly versatile, performed under mild aqueous conditions, and promising for the development of antibacterial, cytocompatible wound dressings.